2017
DOI: 10.3847/1538-4357/aa8326
|View full text |Cite
|
Sign up to set email alerts
|

What Distinguishes the Host Galaxies of Radio-loud and Radio-quiet AGNs?

Abstract: We compare the optical properties of the host galaxies of radio-quiet (RQ) and radio-loud (RL) Type 2 active galactic nuclei (AGNs) to infer whether the jet production efficiency depends on the host properties or is determined just by intrinsic properties of the accretion flows. We carefully select galaxies from SDSS, FIRST, and NVSS catalogs. We confirm previous findings that the fraction of RL AGNs depends on the black-hole (BH) masses, and on the Eddington ratio. The comparison of the nature of the hosts of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 76 publications
1
13
1
Order By: Relevance
“…In these galaxies the contribution from H II regions can be neglected. The results for the cleaned samples (see Kozieł-Wierzbowska et al, 2017) confirm our findings for the whole RL and mRQ samples concerning morphological properties. From the comparison of CI and of the b/a ratio we see that there is a difference in morphology between RL and mRQ galaxies.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…In these galaxies the contribution from H II regions can be neglected. The results for the cleaned samples (see Kozieł-Wierzbowska et al, 2017) confirm our findings for the whole RL and mRQ samples concerning morphological properties. From the comparison of CI and of the b/a ratio we see that there is a difference in morphology between RL and mRQ galaxies.…”
Section: Resultssupporting
confidence: 86%
“…The histograms of plotted parameters for RL and RQ galaxies are also shown. Updated version published inKozieł-Wierzbowska et al (2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We note that this is not what is typically expected, as RQ AGN (at least the ones found at bright > 1 mJy radio fluxes, e.g. see Kozieł-Wierzbowska et al 2017) and SFGs are generally found in lower-mass host galaxies than RL AGN. However, perhaps because of our joint selection based on radio detection and SFR IR estimate, particularly in the higher-redshift bins where most of our sample lies the range of SFRs and thus of stellar masses probed by our sample is limited and biased towards higher values, making it difficult to distinguish different populations.…”
Section: Sfr Vs Stellar Masscontrasting
confidence: 68%
“…It is widely accepted that the broad range in radio powers (up to 4 decades), sizes (up to Mpc scales), and radio morphologies of jet-ted active galactic nuclei (AGNs) stems from the complex interplay between the jet production efficiency (linked to the properties of accretion flow around the supermassive black hole (SMBH) located at the centers of galaxies), interaction of jets with the host galaxy, and the large scale environment they reside in (see, for a recent review, Padovani et al 2017;Blandford et al 2019). While accretion onto the SMBH has been unequivocally accepted as the main source of AGN activity, it is not clear what fraction of it is channeled as kinetic energy of a jet as the majority of the optically selected galaxies and their high luminosity counterparts, quasars, do not show significant radio activity (see Baloković et al 2012;Kozie l-Wierzbowska et al 2017, and references therein). Moreover, the energy exchange between the evolving radio source and the interstellar/intergalactic medium on small as well as large scales forms an important part of the feedback that governs the co-evolution of galaxies, central SMBH, and galaxy groups/clusters over cosmological timescales (see, for a review, McNamara & Nulsen 2007;Fabian 2012).…”
Section: Introductionmentioning
confidence: 99%